2021
DOI: 10.1016/j.ijscr.2021.106495
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal tuberculosis mimicking advanced ovarian cancer case report: Laparoscopy as diagnostic modality

Abstract: Introduction and importance Peritoneal Tuberculosis is one of extrapulmonary tuberculosis that occurs in 1-2% of patients, its incidence is higher in developing countries. It is very difficult to diagnosed and can mimic advanced ovarian cases. Making an accurate diagnosis is vital, laparoscopy is a great modality for this purpose. Case presentation A 36 years-old woman got referred with abdominal distention and weight loss from an internist and digestive surgeon. The ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Any kind of peritoneal disease has been associated with an increased level of CA-125, and hence, it is an unreliable investigation in this case. This is also supported by a similar case report by Purbadi et al, where the CA-125 level was found to be 1,200 U/mL [ 10 ], which is much higher than our case.…”
Section: Discussionsupporting
confidence: 93%
“…Any kind of peritoneal disease has been associated with an increased level of CA-125, and hence, it is an unreliable investigation in this case. This is also supported by a similar case report by Purbadi et al, where the CA-125 level was found to be 1,200 U/mL [ 10 ], which is much higher than our case.…”
Section: Discussionsupporting
confidence: 93%
“…Microscopically, the important diagnostic clue is a large confluent granulomas with central caseous necrosis; while tissue PCR is positive in 25-70%. 7, 10 The results of BTA staining from the pus deep sample showed the formation of BTA positive bacteria and PMN +3 cells, the results of pathological examination showed pieces of connective tissue and fat with groups of epithelioidshaped histiocyte cells that formed granulomas, with datia Langhans cells and lymphocytes scattered at the edges. In the middle, caseous necrosis appears to form soft tubercles.…”
Section: Case Reportmentioning
confidence: 99%
“…8, 9 Especially due to non-specific abdominal or pelvic symptoms such as masses, ascites, that can mimic cases of advanced ovarian cancer. 10 Ovarian carcinoma biomarker, Ca125, has been reported to be elevated in patients with pulmonary and extrapulmonary TB including PTB. 2, 11 A study showed that the serum CA-125 level was elevated approximately 44% of patients with active pulmonary TB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations